Academia y Política: Región e historia para derrotar complicidad. (2019)
The main objective of this article is to share somereflections about the responsibility in the Academy for thepolitical education. In that way the paper is divided in twosections.The first one reviews institutional experience to think ofthese topics. The second one describes punctual questionsabout the Academy role in the political education.